Substitution Buccal Mucosal Graft Urethroplasty for Long Segment Anterior Urethral Stricture : Our Experience in Dorsolateral Onlay Approach - Nandy, Shiba Prasad; Md Asaduzzaman, -; Mazumder, Kamal Uddin; Khan, Sakhawat Mahamud; Ul Hoque, Md Monowar (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background: Currently the most favorable single stage procedure for management of long segment anterior urethral stricture is dorsal onlay technique of urethroplasty. This required circumferential extensive mobilization of the urethra, which might cause ischemia of urethra in addition to chordee. To evaluate the short term outcome of dorsolateral onlay BMG (Buccal Mucosal Graft) urethroplasty by unilateral urethral mobilization for treatment of long segment anterior urethral stricture Materials and methods: A prospective experimental study from January 2016 to December 2018 is carried out in Department of Urology, Chittagong Medical College Hospital (CMCH) Chattogram, Bangladesh. Total 32 patients of long segment anterior urethral stricture were treated by dorsolateral onlay BMG urethroplasty by unilateral urethral mobilization. Stricture >2cm were included; RGU, MCU and Uroflowmetry were the mainstay of assessment. Success was defined as maximum flow rate >15 ml/s, normal RGU and/ urethroscopy. Failure considered as presence of obstructive symptoms, Qmax < 15 ml/s, stricture on RGU and any post-operative urethral intervention. Results: Mean stricture length was 48.72mm (Range: 30-77mm) and mean follow up time was 22.4months (Range: 12-40 months). Three patients were found to develop stricture at proximal anastomotic site during follow up and required optical internal urethrotomy and considered as failure. 01 patients developed Surgical Site Infection (SSI) which resolved after regular dressing. Success rate was 90.7% Conclusion: Dorsolateral onlay BMG urethroplasty by unilateral mobilization is feasible, safe and easily adoptable for long segment anterior urethral stricture with good short term outcome. Chatt Maa Shi Hosp Med Coll J; Vol.20 (2); July 2021; Page 14-17